SMART TRASH Study on RFID tags and the recycling industry - Schindler, Helen Rebecca (RAND Corporation, 2012)
The study aims to assess the environmental impact of the RFID tags themselves as well as the environmental advantages that the use of RFID can provide to product lifecycle management. The Final Report presents the findings of our research.